Electroluminescence and current–voltage measurements of single-(In,Ga)N/GaN-nanowire light-emitting diodes in a nanowire ensemble - van Treeck, David (Beilstein J Nanotechnol, 2019)
We present the combined analysis of electroluminescence (EL) and current–voltage (I–V) behavior of single, freestanding (In,Ga)N/GaN nanowire (NW) light-emitting diodes (LEDs) in an unprocessed, self-assembled ensemble grown by molecular beam epitaxy. The data were acquired in a scanning electron microscope equipped with a micromanipulator and a luminescence detection system. Single NW spectra consist of emission lines originating from different quantum wells, and the width of the spectra increases with decreasing peak emission energy. The corresponding I–V characteristics are described well by a modified Shockley equation. The key advantage of this measurement approach is the possibility to correlate the EL intensity of a single-NW LED with the actual current density in this NW. This way, the external quantum efficiency (EQE) can be investigated as a function of the current in a single-NW LED. The comparison of the EQE characteristic of single NWs and the ensemble device allows for a quite accurate determination of the actual number of emitting NWs in the working ensemble LED and the respective current densities in its individual NWs. This information is decisive for a meaningful and comprehensive characterization of a NW ensemble device, rendering the measurement approach employed here a very powerful analysis tool.